Factors Influencing Alcohol Consumption Among Adult Residents of Tema, Community One in the Greater Accra Region - Frimpong-Mansoh, R.P. (University of Ghana, 2013)
Alcohol consumption is a long lasting widespread and varied man custom. It has become a growing challenge in many African countries of which Ghana is no exception. In spite of the numerous health and social problems associated with its use and abuse, data on alcohol consumption is insufficient and not collected consistently. This informed the inclusion of alcohol questions in the Ghana Demographic and Health Survey, 2008. This study was a cross sectional study of 412 adults aged 18 years and above that sought to determine the proportion and the factors influencing alcohol consumption in Tema Community One. Data was collected using questionnaires and was analyzed by SPSS version 20. The proportion of adults who consumed alcohol in Community One was found to be 50%, men always consumed more alcohol than women. Majority of those who consumed alcohol were within the 18-29 age group. Alcohol consumption was significantly associated with sociodemographic factors (age, sex, educational level, marital status, employment and occupation), income level but not environmental factors. Most people drink alcohol to have fun and cope with stress. They considered alcohol consumption as an adult way of life, as an appetizer or to satisfy partner(s) in bed citing peer influence and advertisement as major contributing factors. Government through the Ministry of Health should enact laws to control the sale and use of alcohol and should be keen on regulating alcohol advertisements in the media.
Thesis (MPH) - University of Ghana, 2013